Strangers : homosexual love in the 19th century / Graham Robb. - Robb, Graham, 1958- (Picador, 2003)
'Strangers' presents a history of homosexuality in the 19th century covering both Europe and America. Topics covered include: the treatment of homosexuals, both male and female, by the rest of society; the lives and loves of gay men and women and the early gay rights movement.